Negative theology and science in the thought of Siemion Frank - Obolevitch, Teresa (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
Siemion Frank (1877-1950) considered the Universe as an ’all-unity’. According to him, everything is a part of the all-unity which has a divine character. God is present in the world but his nature is incomprehensible. In this article the author analyzes two consequences of Frank’s panentheistic view concerning the relation between science and theology. Firstly, limits of scientific knowledge allow to emphasize the mystery of the world and the transcendence of God. Secondly, Frank claims that the nature is a ’trace’ of God and the manifestation of the absolute reality, i.e., all-unity. As a result, both science and theology lead to the knowledge of God, although his essence remains inaccessible.